The traditional, the ideal and the unexplored: sport coaches' social identity constructs in film. Issue 1 (2nd January 2016) - Jolly, Sue; Lyle, John
Abstract: The sport coaching construct within mainstream fiction films has been described as stereotypical, reinforcing the traditional notion of the sport coach as a technician who conquers all, or a hapless individual, open to ridicule from athletes and fans. Although this depiction is also prevalent in some independent fiction films and documentaries, film sub genres such as social realism and "fly on the wall" style documentaries move away from the "Hollywood sports film structure" towards stories that focus on everyday coaching moments. Through a critical discourse analysis of two U.K. films ( Bend it Like Beckham and Twenty Four Seven ), both featuring sport coaches in central roles, we reflect critically on these mass media multidimensional representations in terms of the sport coaching professionalisation agenda in the U.K. and the social identification process of sport coaches within their sporting environments.